How to become a superstar student / course guidebook - Geisen, Michael (Chantilly, VA : The Great Courses, 2011)
A former award-winning middle school science teacher provides tips on study skills for high school students to improve their academic achievement. Parent participation is also discussed.
Complimentary copy from PDC
Keywords: Study skills; Self-culture; Education, Secondary -- Parent participation; Academic achievement